Eduard Gans sobre a pobreza e o debate constitucional (Revista Eletrônica Estudos Hegelianos, 2020)
Eduard Gans (1797–1839) remains so far a neglected thinker, even though he was considered at his time the most talented of Hegelians. Since he was afterwards regarded a mere populariser of Hegel, many of Gans’ original contributions have been completely overshadowed. In order, therefore, to contribute to the redis-covery of Gans’ original contributions, this arcticle will focus on two debates that lie at the heart of his political thought: the social question of poverty and the constitutional issue in Prussia. We shall see that Gans’ answer to the social question reveals not only a gradual maturation, but also a significant distinction between a pre- and a post-1830 period, meaning that Gans thereby gradually departed from Hegel’s perspective and – as he approached Saint-Simonian theories of association without its collectivist implications – anticipated a proto-unionist per-spective. With regard to the constitutional issue, we shall see that Gans, by exploring the gap between the con-sciousness of freedom and its realization, turned himself critically to the Prussian state and developed a “theory of opposition” envisaging an ideal of a parliament divided into government and opposition.